The effects of acamprosate and neramexane on cue-induced reinstatement of ethanol-seeking behavior in rat - Bachteler, Daniel; Economidou, Daina; Danysz, Wojciech; Ciccocioppo, Roberto; Spanagel, Rainer (Neuropsychopharmacology, 2005)
This study examines, for the first time, the effects of acamprosate and the non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist neramexane on ethanol-seeking induced by alcohol-related environmental stimuli in an animal model of relapse. Wistar rats were trained to operantly self-administer ethanol (10% w/v) or water on a fixed-ratio 1 schedule in a 30-min daily session. Ethanol availability was signaled by an olfactory discriminative stimulus of orange extract (S+). In addition, each lever press was accompanied by a 5-s illumination of the operant chamber's house light (CS+). Water availability was signaled by anise odor (S−) and 5-s white noise stimulus (CS−). After completion of the conditioning phase, indicated by stable levels of responding, operant behaviors were extinguished. Prior to reinstatement tests, animals were divided into groups according to either treatment with acamprosate (100, 200 mg/kg given twice), neramexane (1.0, 2.0, 4.0 mg/kg), or vehicle. In vehicle-treated rats, re-exposure to the S+/CS+ in the absence of further ethanol availability elicited strong recovery of responding. No effect was observed following presentation of water-paired cues (S−/CS−). Acamprosate dose-dependently attenuated recovery of responding elicited by ethanol-paired cues (S+/CS+), whereas responding under S−/CS− was not modified by drug administration. Treatment with 1.0 and 2.0 mg/kg of neramexane did not significantly modify responding under both S+/CS+ and S−/CS− conditions. However, a slight reduction of cue-induced reinstatement of alcohol seeking was observed. At the dose of 4.0 mg/kg, neramexane elicited a marked inhibition of responding following presentation of both ethanol- and water-paired cues. In conclusion, acamprosate significantly and selectively reduced alcohol-seeking elicited by environmental stimuli predictive of alcohol availability. Treatment with neramexane that shares part of the pharmacological effects of acamprosate on NMDA receptors, however, resulted in a nonselective reduction of lever responding.
Gesehen am 22.10.2020